4-(octyloxy)-N-(4-hexylphenyl)-2-hydroxybenzalimine thermotropic compound:: Morphologic, mesomorphic, thermotropic, thermooptical and thermodynamical properties - Nesrullajev, Arif; Eran, Belkiz Bilgin; Yorur, Cidem (WORLD SCIENTIFIC PUBL CO PTE LTD, 2008)
In this work, the mesomorphic, morphologic, thermotropic, thermooptical, and thermodynamical properties of 4-(octyloxy)-N-(4-hexylphenyl)-2-hydroxybenzalimine thermotropic liquid crystalline compound, which was synthesized by our group, have been studied in detail. This compound displays smectic C and nematic mesophases. These mesophases are enantiotropic and exhibit specific confocal and schlieren textures, respectively. Thermotropic, thermooptical, and thermodynamical properties of the compound at direct and reverse phase transitions between smectic C and nematic mesophases and also between nematic mesophase and isotropic liquid have been investigated. The peculiarities of the bistable heterophase regions of these phase transitions have been studied.
Keywords: optical materials; organic compounds; optical properties; phase transactions; thermodynamic properties; LIQUID-CRYSTALLINE PROPERTIES; PHASE-TRANSITIONS; COMPLEXES; ORDER; DSC; Physics